The Influence of Financial Well‐Being on Pawnshop Use. Issue 4 (5th March 2019) - Nicolini, Gianni; Cude, Brenda J.
Abstract : This research examined the influence of financial well‐being on pawnshop use. Data from the 2015 National Financial Capability Study were used to construct a measure of financial well‐being, based on the Consumer Financial Protection Bureau's definition. A higher financial well‐being reduced the odds of pawnshop use by 17%, even after controlling for having a bank account, having a credit card, being financially overconfident, proximity to local pawnshops, and selected demographic characteristics. The authors make recommendations for future research based on changes in the pawnshop industry and its users.